Ying Jin, Doctor–Patient Communication in Chinese and Western Medicine (London, Routledge, 2024, 184 pp. ISBN 978-0-367-75309-2) (Altre Modernità, 2025)
Ying Jin, Doctor–Patient Communication  in Chinese and Western Medicine  (London, Routledge, 2024, 184 pp. ISBN 978-0-367-75309-2)by Alessandro Vallati